Simple sugars in fruit and the presence of colorectal cancers and polyps - Piotr Sikorski; Małgorzata Szamocka; Agnieszka Meder; Monika Anna Ameryk; Maciej Świątkowski (Kazimierz Wielki University, 2017)
The current knowledge based on facts provides data regarding genetic and environmental factors relevant for malignancies, including colorectal cancer (CRC) which frequently occurs in well-developed countries. CRC carcinogenesis, a process often lasting 10 to 20 years, has been elucidated.                                                                                                                       The aim of the study was to evaluate the role of simple sugars contained in fruit in the development of colorectal cancer and polyps.                          The study group consisted of 106 people aged 66 years and older. Colonoscopy screening was used as an opportunistic examination. Among people not qualified for the examination were those with diagnosed disease organic disease of the large intestine, suspected CRC, and people with poor health status due to diagnosed advanced organic diseases of essential organs. Colonoscopy screening was conducted at the Clinic of Gastroenterology and Nutrition Disorders, Collegium Medicum in Bydgoszcz.                                                                                       The project demonstrated that in the group of 106 elderly people, in whom colonoscopy was conducted as an opportunistic examination under PBP, CRC was detected in 6 subjects, which is significantly more compared to 1 person in the control group. Apart from subjects with CRC, additional 8 subjects had histologically advanced adenomas that due to the high degree of dysplasia and/or presence of a villous component constituted a real risk of developing CRC in the future. In the control group, whose average age was 10 years younger, only one person was found to have cancer and other two had advanced adenomas, and while more adenomas were detected in the study group, they did not pose a significant risk of CRC.                                                                                               The results obtained in the study allow us to draw the conclusion that in order to reduce the likelihood of developing colorectal cancer in older age, proper lifestyle habits should be promoted from childhood and based on rational nutrition, safe and functional food products and, inseparably, physical activity, with colonoscopy screening conducted once in ten years starting from the age of 50.